Tribological properties of nanolamellar tungsten disulfide doped with zinc oxide nanoparticles - An V. V. Vladimir Vilorievich; Irtegov Yu. A. Yuri Aleksandrovich; Anisimov E. E. Evsey Evseevich; Druzjyanova V. P. Varvara Petrovna; Burtsev N. N. Nikolay Nikolaevich; Khaskel'berg M. B. Mikhail Borisovich (2015, 2015)
Title screen